2013
DOI: 10.1002/14651858.cd009243.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Antispasmodics for labour

Abstract: Analysis 2.3. Comparison 2 Antispasmodics versus control: studies including caesarean section versus studies excluding C/S in analysis, Outcome 3 Duration of third stage of labour (min).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…A Cochrane review reported that intrapartum antispasmodics significantly accelerate the first stage of labor by increasing the cervical dilatation rate without compromising the durations of the second and third stages of labor or the rate of normal vertex deliveries . The current study demonstrated that metoclopramide significantly reduced the duration of the first stage of labor and increased the cervical dilatation rate.…”
Section: Discussionsupporting
confidence: 52%
“…A Cochrane review reported that intrapartum antispasmodics significantly accelerate the first stage of labor by increasing the cervical dilatation rate without compromising the durations of the second and third stages of labor or the rate of normal vertex deliveries . The current study demonstrated that metoclopramide significantly reduced the duration of the first stage of labor and increased the cervical dilatation rate.…”
Section: Discussionsupporting
confidence: 52%
“…Modern times, "Active Management" trends towards curtailing the total duration of labour compatible with the safety of the mother and foetus. 1 Drotaverine, an isoquinoline derivative, inhibits specifically phosphodiesterase IV (PDE IV) which in turn increases the intracellular concentration of cAMP and cGMP and causes smooth muscle relaxation. Inj.…”
Section: Introductionmentioning
confidence: 99%
“…In a Cochrane review known as "antispasmodic for labor" (2013), it was stated that there was no statistical significant relationship between musculotropic drugs with tachycardia, fetal distress, fetal tachycardia and bradycardia, admission to NICU, mouth dryness, headache, nausea, vomiting, dizziness, giddiness, and meconium-stained liquor, but flushing of face and postpartum hemorrhage were significant [3]. Promethazine is an antihistamine and is derived from phenothiazine (H1 receptor inhibitor) and can have a similar effect as anticholinergic and antimuscarinic drugs on inhibiting acetylcholine receptor.…”
Section: This Article Is Part Of the Topical Collection On Medicinementioning
confidence: 99%
“…In the delivery room (especially in Zanjan-Iran hospitals), promethazine is used to reduce nausea [27], to sedate [28], and to relieve pain [29,30]. In a Cochrane systematic review titled as "antispasmodic for labor," 21 articles were analyzed (with 3286 participants) and no side effects and neonatal risks of this drug were mentioned [3].…”
Section: This Article Is Part Of the Topical Collection On Medicinementioning
confidence: 99%
See 1 more Smart Citation